Primary Leiomyosarcoma of left sided colon: a case report - Mishra, R; Dhakal, S K S; Rai, P; Bhattacharya, S; Rai, N; Ghimire, S; Koirala , N (Nepal Mediciti Medical Journal, 2024)
Leiomyosarcomas are rare smooth muscle tumors that represent 0.1% of all colorectal malignancies. The lack of literature available concerning leiomyosarcomas presents a challenge when diagnosing and treating these tumors, thus it is crucial that we differentiate them from gastrointestinal stromal tumors (GIST), the most common type of mesenchymal neoplasms of the gastrointestinal (GI) tract, especially when considering leiomyosarcoma's high prevalence of recurrence and malignancy. In this article, we present a case of a 69-year-old female with a diagnosis of sigmoid colon leiomyosarcoma. We analyze the tumor's CT imaging findings as well as correlation with the patient's pathological findings including immunostains, size, and mitotic activity, as well as the patient's risk for recurrence.